2016
DOI: 10.1007/s12663-016-0898-2
|View full text |Cite
|
Sign up to set email alerts
|

Open Access Publishing: A Study of Current Practice in Oral and Maxillofacial Surgery Research

Abstract: Introduction Open access (OA) publication has become an increasingly common route for dissemination of scientific research findings. However, it remains a contentious issue with continued debate as to its impact on the peer-review process and a potential change in the quality of subsequent evidence published. There is little research that looks into OA in oral and maxillofacial surgery. Methods We investigated the OA policy in the 30 relevant journals listed in the Institute for Scientific Information Web of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Our analysis showed that there was no significant association of free article access with AAS. This is in agreement with bibliometric studies in dentistry and oral and maxillofacial surgery, in which no significant differences in citations were found between open access and pay‐for‐access articles (Gaule & Maystre, ; Tahim, Bansai, Goodson, Payne, & Sabharwal, ). Apparently, other factors than accessibility of research work motivate readers to disseminate or recommend scholarly material online.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analysis showed that there was no significant association of free article access with AAS. This is in agreement with bibliometric studies in dentistry and oral and maxillofacial surgery, in which no significant differences in citations were found between open access and pay‐for‐access articles (Gaule & Maystre, ; Tahim, Bansai, Goodson, Payne, & Sabharwal, ). Apparently, other factors than accessibility of research work motivate readers to disseminate or recommend scholarly material online.…”
Section: Discussionsupporting
confidence: 90%
“…were found between open access and pay-for-access articles (Gaule & Maystre, 2011;Tahim, Bansai, Goodson, Payne, & Sabharwal, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…One of the methods to evaluate the impact in applied science can be through bibliometric analysis. Bibliometric analysis has been performed in various sub-specialties of dentistry including periodontology [29], oral and maxillofacial surgery [30], implantology [31], orthodontics [32], prosthodontics [33], pediatric dentistry [34], and endodontics [35]. However, the authors could not find any bibliographic study where studies on antibacterial dental adhesive were assessed quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Tahim et al [122] studied the OA policy of 30 SCIE-indexed, oral and maxillofacial surgery-related journals (including implant dentistry and head and neck surgery), and found that three (10%) of these journals were full OAJs, twenty (67%) were Hybrid OA, and the rest (23%) did not offer researchers any OA publishing services. They made a comparison of the impact factor and level of evidence (LOE) between journals offering OA publishing (both OAJs and Hybrid OA journals) and the others, and found no significant differences.…”
Section: Current Situation Of Oa In Dentistrymentioning
confidence: 99%